Aspek Hukum Pelanggaran Hak Anak atas Praktik Perjanjian Top Up Game Online oleh Anak di Bawah Umur dan Perlindungan terhadap Anak - Sabrina, Sabrina; Iman, Candra Hayatul; Zubaedah, Rahmi; Apriani, Rani (Peneliti.net, 2026)
The development of information technology in the digital age has given rise to the phenomenon of widespread online game top-up practices by minors. This practice raises legal issues because children, as legal subjects, are categorised as incapable of entering into agreements according to Article 1330 of the Civil Code. This study aims to analyse the legal aspects of violations of children's rights related to online game top-up agreements, identify their legal consequences, and examine protective measures for children in this context. This study employs a legal research method with an empirical legal approach, collecting data through a literature review of regulations and legal doctrines. The findings reveal that top-up agreements made by minors do not meet the legal requirements for a valid agreement and may lead to legal uncertainty, fraud risks, and negative impacts on children's psychosocial development. Mitigation efforts must be undertaken in a multidimensional manner, through regulatory updates, strengthening age verification mechanisms, the responsibility of digital platform providers, active parental involvement, and digital literacy among the public. This study is expected to serve as an academic and practical reference to support the strengthening of child protection in electronic transactions in the digital age.